Acne vulgaris: pathogenesis and treatment. Consensus of the Polish Dermatological Society - Szepietowski, Jacek; Kapińska-Mrowiecka, Monika; Kaszuba, Andrzej; Langner, Andrzej; Placek, Waldemar; Wolska, Hanna; Matusiak, Łukasz (Dermatology Review/Przegląd Dermatologiczny, 2012)
Acne vulgaris is the most common skin disorder. Taking into consideration the increasing number of available treatment modalities, we attempted to systematize current therapeutic strategies available in Poland. These recommendations were established to help Polish dermatologists care for patients with this disease. In this consensus we describe updated views on the pathogenesis of acne and the eligibility of patients for topical or systemic therapy depending on the severity of clinical manifestations. We do hope that our recommendations will be valuable for the physicians in their daily clinical practice. However, we would like to underline that the final decision about treatment modality should always be made individually for every patient, based on the patient’s current clinical status and also taking into account the most up-to-date scientific literature data.